The science and politics of ‘knowledge’ in safe sport research - Benjamin Carr (Current Issues in Sport Science)
Research in the domain of safe sport frequently focuses on prevalence studies that have been historically dissimilar in methodology. Attempting to unify future studies for comparable results, Parent et al. (2018) introduced and validated the Violence Towards Athletes Questionnaire (VTAQ). The epistemological critiques of what knowledge this, or any, research tool generates about the sensitive topic of violence in sport has not been fully investigated. Additionally, how this ‘knowledge’ is used and by whom leads to further reconsideration about the validity of the data the VTAQ generates. Lastly, a brief discourse review illustrates how athletes’ capital may be appropriated to reinforce claims of validity and exclusivity of knowledge.